Australasian Parliamentary Debate Strategy to Foster Students’ Speaking Competence - Ulil Fuadah; Sri Rachmajanti; Fracisca Maria Ivone (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Teaching English needs an appropriate strategy to effectively enhance the students' communicative competence, especially speaking competence. When the teaching process does not use the appropriate strategy, the students will meet the barriers to achieving the instructional goals. Based on the preliminary study conducted to the second grade of Islamic Senior High School of Blitar, the researcher found some students' speaking problems. Therefore, the Australasian Parliamentary Debate was proposed as a strategy to overcome those problems by conducting Classroom Action Research. After implementing the strategy of Australasian Parliamentary Debate in multimodal teaching-learning process, the study needed two cycles to overcome the students' speaking problems and improve the students' speaking skill.Abstrak: Mengajar bahasa Inggris membutuhkan strategi yang tepat agar mampu meningkatkan kemampuan siswa dalam kompetensi komunikatifnya, khususnya kompetensi berbicara. Apabila pembelajaran tidak menggunakan strategi yang tepat, maka siswa akan mengalamai kesulitan untuk mencapai tujuan pembelajaran yang diharapkan. Sesuai dengan hasil observasi yang dilakukan di kelas dua MAN Kota Blitar, peneliti menemukan beberapa permasalahan siswa dalam berbicara. Oleh karena itu, peneliti mencoba menerapkan strategi Debat Parlementer Australia untuk mengatasi permasalahan yang dihadapi siswa dalam belajar berbicara. Setelah penerapan strategi tersebut, dengan menekankan pada proses pembelajaran berbasis multimodal, peneliti membutuhkan dua siklus untuk dapat mengatasi permasalahan yang dihadapi siswa dan meningkatkan kemauan berbicara mereka.